Respuesta :

Step 1 : We have the following equation: 3x - 3 = 4x + 2​

Step 2: Let's solve it, this way:

A. Like terms (Variable x and coefficients on the left and integers on the right)

3x - 4x = 2 + 3

-x = 5

Multiplying by - 1 at both sides, we have:

-x (-1) = 5 (-1)

x = -5

Step 3: Let's prove that x = -5 is correct, this way:

3x - 3 = 4x + 2

3 (-5) - 3 = 4 (-5) + 2

-15 - 3 = -20 + 2

- 18 = - 18

We just proved that x = -5 is correct for the equation given!

My pleasure to help you out today, Devin!